2006
DOI: 10.1002/ajmg.b.30331
|View full text |Cite
|
Sign up to set email alerts
|

No association between the Ser9Gly polymorphism of the dopamine D3 receptor gene and schizophrenia in a Spanish sample

Abstract: This study aims to further evaluate the controversial association between the Ser9Gly polymorphism in codon 9 of the D3 dopamine receptor gene (DRD3) and schizophrenia in psychiatric inpatients acutely hospitalized in two general hospitals in Madrid, Spain. The Ser9Gly polymorphism of the DRD3 was examined in 178 schizophrenic patients, 286 patients with other psychiatric diagnoses, and 132 controls recruited. Genotype frequencies were in Hardy-Weinberg equilibrium. No association was found between schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Case and control ascertainment and clinical evaluations were standardized between sites as described previously (Baca-Garcia, Oquendo, Saiz-Ruiz, Mann, & de Leon, 2006). Genetic data from subsets of these research participants have been used in previous studies with different research objectives (Almoguera et al, 2011; Almoguera et al, 2013a, 2013b; Alonso et al, 2008; Baca-Garcia et al, 2005; Baca-Garcia et al, 2003; Baca-Garcia, Vaquero, Diaz-Sastre, Garcia-Resa, et al, 2004; Baca-Garcia, Vaquero, Diaz-Sastre, Jimenez-Trevino, et al, 2004; Baca-Garcia et al, 2002; Baca-Garcia et al, 2007; Baca-Garcia et al, 2010; Bermudo-Soriano et al, 2009; Blasco-Fontecilla et al, 2013; Costas et al, 2010; Fernandez-Navarro et al, 2012; Gratacos et al, 2009; Lopez-Castroman et al, 2009; Lorenzo et al, 2007; Penas-Lledo et al, 2012; Perroud et al, 2010; Sublette et al, 2008; Vaquero et al, 2004; Vaquero Lorenzo et al, 2006; Vaquero-Lorenzo et al, 2008; Vaquero-Lorenzo et al, 2014; Vaquero-Lorenzo et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Case and control ascertainment and clinical evaluations were standardized between sites as described previously (Baca-Garcia, Oquendo, Saiz-Ruiz, Mann, & de Leon, 2006). Genetic data from subsets of these research participants have been used in previous studies with different research objectives (Almoguera et al, 2011; Almoguera et al, 2013a, 2013b; Alonso et al, 2008; Baca-Garcia et al, 2005; Baca-Garcia et al, 2003; Baca-Garcia, Vaquero, Diaz-Sastre, Garcia-Resa, et al, 2004; Baca-Garcia, Vaquero, Diaz-Sastre, Jimenez-Trevino, et al, 2004; Baca-Garcia et al, 2002; Baca-Garcia et al, 2007; Baca-Garcia et al, 2010; Bermudo-Soriano et al, 2009; Blasco-Fontecilla et al, 2013; Costas et al, 2010; Fernandez-Navarro et al, 2012; Gratacos et al, 2009; Lopez-Castroman et al, 2009; Lorenzo et al, 2007; Penas-Lledo et al, 2012; Perroud et al, 2010; Sublette et al, 2008; Vaquero et al, 2004; Vaquero Lorenzo et al, 2006; Vaquero-Lorenzo et al, 2008; Vaquero-Lorenzo et al, 2014; Vaquero-Lorenzo et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) in the first exon of the dopamine D3 receptor gene, the Ser9Gly polymorphism (the Ser9 variant refers to allele 1, and the Gly9 variant is identified as allele 2), gives rise to a serine to glycine substitution in the N‐terminal extracellular domain of the receptor protein and it is supposed to be associated with a twofold higher risk of schizophrenia when two mutant alleles are present in a homozygote [Lundstrom and Turpin, 1996; Tanaka et al, 1996; Wong et al, 2000; Hellstrand et al, 2004]. Most of the studies have not shown any evidence for the association between the serine for glycine substitution and high risk of schizophrenia [Jönsson et al, 1993; Yang et al, 1993; Di Bella et al, 1994; Durany et al, 1996; Chen et al, 1997; Hawi et al, 1998; Joober et al, 2000; Virgos et al, 2001; Anney et al, 2002; Chang et al, 2007; Lorenzo et al, 2007; Fathalli et al, 2008], but several meta‐analyses have reported an association between Ser9Gly variation and schizophrenia [Mant et al, 1994; Kennedy et al, 1995; Dubertret et al, 1998; Williams et al, 1998; Jönsson et al, 2003]. Genetic variations in that gene might account for significantly higher dopamine binding affinity and interindividual differences in response to drugs [Ilani et al, 2001; Jönsson et al, 2003; Bakker et al, 2006].…”
Section: Introductionmentioning
confidence: 99%